If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -10x = 2(-7x + 6) Reorder the terms: -16 + -10x = 2(6 + -7x) -16 + -10x = (6 * 2 + -7x * 2) -16 + -10x = (12 + -14x) Solving -16 + -10x = 12 + -14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '14x' to each side of the equation. -16 + -10x + 14x = 12 + -14x + 14x Combine like terms: -10x + 14x = 4x -16 + 4x = 12 + -14x + 14x Combine like terms: -14x + 14x = 0 -16 + 4x = 12 + 0 -16 + 4x = 12 Add '16' to each side of the equation. -16 + 16 + 4x = 12 + 16 Combine like terms: -16 + 16 = 0 0 + 4x = 12 + 16 4x = 12 + 16 Combine like terms: 12 + 16 = 28 4x = 28 Divide each side by '4'. x = 7 Simplifying x = 7
| (x-7)*(x-6)= | | X-6=2x+12 | | 2/3x^2+7/3=5 | | d+c+(b-10)+(b+10)=360 | | (x-7)*(x+6)= | | 2a^2-a-12=2 | | 7m+15=9m-75 | | (4/8)(2/3)(1/5) | | X-6=2x-24 | | u(6u+5)=1 | | 6=-15x | | (3/5-3/10)*30 | | 76=-4m | | h=-16t^2+56t+40 | | x^3/2=14 | | 2(3.14)(12)= | | 0.125x=-3 | | b/2+5=-7 | | Y/3=15 | | 8c=-122 | | 2(z-x)=5x-(3x+2) | | 25/57=849/5x | | w^8+11w^4+10= | | 7x+5y=9 | | y=2/5-2 | | 8b+11-3b=2b-3+5 | | 3/4x-7=17 | | 4x^2+17=5 | | (45-27)n= | | x+1/3+x+2/7=2 | | 14-3(5t-12)=1-(29t+1) | | 3x-(2x-7)=3(1+x) |